פתרון :? 5 = 1 (1 + 1 / (x ^ 2 + y ^ 2)) = 12 ו- 5y (1 - 1 / (x ^ 2 + y ^ 2)) = 4

פתרון :? 5 = 1 (1 + 1 / (x ^ 2 + y ^ 2)) = 12 ו- 5y (1 - 1 / (x ^ 2 + y ^ 2)) = 4
Anonim

תשובה:

ראה את התשובה למטה …

הסבר:

# 5x (1 + 1 / (x ^ 2 + y ^ 2)) = 12 ##color (אדום) "|" ## 5y (1-1 / (x ^ 2 + y ^ 2)) = 4 #

# => (1 + 1 / (x ^ 2 + y ^ 2)) = 12 / (5x) ##color (אדום) "|" ## => (1-1 / (x ^ 2 + y ^ 2)) = 4 / (5y) #

משתי המשוואה,

#color (אדום) (12 / (5x) + 4 / (5y) = 2 #

# => 12 / (5x) = 2-4 / (5y) #

# => 6 / (5x) = 1-2 / (5y) #

# => (5x) / 6 = (5y) / (5y-2) #

# => x = (6y) / (5y-2) #

לשים את זה במשוואה הראשונה, # 5 (6) / (5y-2)) (2) (2)

עזור לי עכשיו.

תשובה:

ראה למטה.

הסבר:

# x ^ 2 + y ^ 2 = (5x) / (12-5x) #

# x ^ 2 + y ^ 2 = (5y) / (5-5y) #

עכשיו

# (5x) / (12-5x) = (5y) / (4-5y) rRrr x = 3y # לאחר מכן

# (3y) ^ 2 + y ^ 2 = (5y) / (5-5y) rRrr 10y = 5 / (4-5y) #

# 1 = {(1/10 (4-sqrt6)), (1/10 (4 + sqrt6)):} #

#x = {(1/30 (4-sqrt6)), (1/30 (4 + sqrt6)):} #